Analysis Of Haruan (Channa Striatus) Water Extract And The Study Of Haruan Aerosol On Wound Healing - ., Lia Laila (2011)
The enhancement of wound healing properties of haruan water extract has been studied. The in vitro and in vivo studies using cell line and animal model were carried out to evaluate the effectiveness of the extract. Analytical study of haruan water extract was conducted to determine the amino acid and fatty acid contents. The determination of the amino acid in haruan water extract was carried out using acid hydrolysis method, followed by AQC pre-column derivatization and analysed using high performance liquid chromatography equipped with fluorescence detector, while the fatty acid determination was performed using acid methylation method with gas chromatography equipped with flame ionization detector.